2015
DOI: 10.5539/jsd.v8n8p133
|View full text |Cite
|
Sign up to set email alerts
|

Tanjung Datu National Park, Sarawak: Communities’ Perceptions towards Its Rural Competitive Advantage

Abstract: Rural tourism is a rapidly growing tourism segment and has been given increasing importance, in view of its potential to contribute economic growth to the rural areas. However, any rural tourism destination development should be implemented in a way that maximizes destination competitive advantage. This study examine the relationship between stakeholder involvement, community knowledge about tourism, and the economic, socio-cultural and environmental impacts on tourism with rural competitive advantage, as perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
(31 reference statements)
1
4
0
Order By: Relevance
“…This study also supports H3 . The findings for environmental impacts were consistent with the findings from a study done in Tanjung Datu (Lo et al , 2015). This is due to the similarity of nature-based setting of tourism at both locations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study also supports H3 . The findings for environmental impacts were consistent with the findings from a study done in Tanjung Datu (Lo et al , 2015). This is due to the similarity of nature-based setting of tourism at both locations.…”
Section: Discussionsupporting
confidence: 89%
“…Lack of knowledge and capabilities to manage stakeholder relationship affected local community perception, where there was less or no stakeholder involvement in tourism development. The finding was contradicted with the study in Tanjung Datu (Lo et al , 2015) of which stakeholders play a major role in creating the source of competitive advantage for rural tourism.…”
Section: Discussionmentioning
confidence: 65%
“…Rural tourism is a rapidly expanding tourism segment with the potential to contribute to economic growth (Lo et al, 2015). However, the development of rural tourism destinations must be carried out in a way that maximizes the objectives of competitive advantage (Neto, 2003;Sharpley, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the development of rural tourism destinations must be carried out in a way that maximizes the objectives of competitive advantage (Neto, 2003;Sharpley, 2002). The findings showed that stakeholder involvement in tourism, community knowledge about tourism and the environmental impact of tourism has a significant positive impact on rural competitive advantage, while the economic and socio-cultural impacts of tourism, as well as community support for tourism have little influence (Lo et al, 2015;Stylidis et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation